The Influence of Internal Control System, Whistleblowing System, and Spiritual Intelligence in the Prevention of Village Fund Management Fraud (Empirical Study on Villages in West Lombok Regency) - Apriana, Rika; Lestari, Baiq Anggun Hilendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
By focusing on the internal control system, whistleblowing system, and spiritual intelligence, this study aims to determine the factors that can influence fraud prevention in the management of village funds in West Lombok Regency. This research consists of primary data collected through questionnaires distributed directly to 55 villages in West Lombok Regency. In addition, secondary data can be obtained from official documents, books, and scientific journals. Data measurement uses a Likert scale of 1 to 5 which is analyzed with partial least square (PLS), namely SmartPLS 4.1 software. The results of this study indicate that the internal control system affects the prevention of fraud in the management of village funds in West Lombok Regency, and spiritual intelligence affects the prevention of fraud in the management of village funds in West Lombok Regency. Meanwhile, the whistleblowing system has no effect on preventing fraud in the management of village funds in West Lombok Regency. This shows that a better internal control system in the village can prevent fraud because it functions as a controller in finding and preventing suspicious actions, so the possibility of fraud is reduced. Higher levels of spiritual intelligence can also help a person be more self-controlled, which can help improve ethics and morality in the workplace and prevent cheating. However, despite a good whistleblowing system, many people are still reluctant to report fraud. This may be because whistleblowers do not trust the current system and fear retaliation in the future if they report fraud.